Basics of budgeting - Dickey, Terry (Crisp Pub. Menlo ParkUS, 1992)
Explains fundamental concepts of budgeting, and provides proven tips and techniques. Supplies examples of calculations and presentation. Outlines the planning process as follows, and provides the methodology for each step: managing the planning process as a whole; strategic plans; the annual operating plan; balance sheet and cash flow planning; budget reviews, budget processes and adjusted plans; and, forecasts and control.